Endoplasmic Reticulum-associated Degradation of Niemann-Pick C1: EVIDENCE FOR THE ROLE OF HEAT SHOCK PROTEINS AND IDENTIFICATION OF LYSINE RESIDUES THAT ACCEPT UBIQUITIN - Nakasone, Naoe (American Society for Biochemistry and Molecular Biology, 2014)
Most cases with Niemann-Pick disease type C carry mutations in NPC1. Some of the mutations, including the most frequent I1061T, give rise to unstable proteins selected for endoplasmic reticulum-associated degradation. The purpose of the current study was to shed mechanistic insights into the degradation process. A proteasome inhibitor MG132 prolonged the life span of the wild-type NPC1 expressed in COS cells. The expressed protein associated with multiple chaperones including heat shock protein 90 (Hsp90), Hsp70, heat shock cognate protein 70 (Hsc70), and calnexin. Accordingly, expression of an E3 ligase CHIP (carboxyl terminus of Hsp70-interacting protein) enhanced MG132-induced accumulation of ubiquitylated NPC1. Co-expression and RNAi knockdown experiments in HEK cells indicated that Hsp70/Hsp90 stabilized NPC1, whereas Hsc70 destabilized it. In human fibroblasts carrying the I1061T mutation, adenovirus-mediated expression of Hsp70 or treatment with an HSP-inducer geranylgeranylacetone (GGA) increased the level of the mutant protein. In GGA-treated cells, the rescued protein was localized in the late endosome and ameliorated cholesterol accumulation. MALDI-TOF mass spectrometry revealed three lysine residues at amino acids 318, 792, and 1180 as potential ubiquitin-conjugation sites. Substitutions of the three residues with alanine yielded a mutant protein with a steady-state level more than three times higher than that of the wild-type. Introduction of the same substitutions to the I1061T mutant resulted in an increase in its protein level and functional restoration. These findings indicated the role of HSPs in quality control of NPC1 and revealed the role of three lysine residues as ubiquitin-conjugation sites.